Liver haematoma in pregnancy: A rare complication of HELLP syndrome (Journal of Kathmandu Medical College, 2021)
Liver haematoma complicating pregnancy with HELLP syndrome is a rare but life-threatening condition. Diagnosis requires a high index of suspicion. Here a case of liver haematoma is presented in a 29 years multigravida at 34 weeks of pregnancy. Initially hypertension was not revealed since she had presented in shock. She had presented with on and off epigastric pain for many days. In context of haemoperitoneum in ultrasound, emergency laparotomy was done and liver haematoma diagnosed intraoperatively. Haematoma was managed with packing and second look laparotomy was done to remove the packs. Haematoma gradually resolved over period of months.